Acute respiratory failure due to eosinophilic pneumonia following pneumococcal vaccination. Issue 12 (2nd December 2019) - Kikuchi, Ryota; Iwai, Yuki; Watanabe, Yusuke; Nakamura, Hiroyuki; Aoshiba, Kazutetsu
ABSTRACT: A 68-year-old woman under maintenance hemodialysis was admitted to our hospital with fever and dyspnea that had developed two days after the second vaccination with the 23-valent pneumococcal polysaccharide vaccine (PPV23). She had received the first vaccination with PPV23 five years earlier without any complications. Chest X-ray and computed tomography (CT) showed bilateral diffuse infiltrative and ground glass opacities. Bronchoalveolar lavage (BAL) revealed an abundance of eosinophils. A positive test result for PPV23 was obtained in the drug lymphocyte stimulation test. The patient was diagnosed as having eosinophilic pneumonia caused by the pneumococcal vaccination and was successfully treated by 3-week's administration of a steroid. No disease recurrence was observed at the three-month follow-up. Thus, EP is a rare, but life-threating condition following pneumococcal vaccination.